(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
This research aimed to estimate the distribution efficiency and optimality of productive resources for yellow corn (autumn crop) in Nineveh Governorate, specifically in Al-Ba’aj district, for the 2023 production season. A random sample of 75 farmers was selected, and data related to production and productive resources were collected, including (cultivated area (x1), seed quantity (x2), fertilizers (x3), human labor (x4), machinery (x5), and irrigation hours (x6)). Using quantitative analysis methods and some mathematical indicators, the production function and distribution efficiency were estimated. The double logarithmic function was chosen as the best model to represent the relationship between the studied variables.The analysis results indicated that the distribution efficiency for some productive resources (x4, x3, x2) was less than one, meaning that the added cost exceeds the added return, indicating waste in resource use and the need to reduce the use of these productive resources. In contrast, the distribution efficiency for resources (x6, x5) was greater than one, meaning that the added return exceeds the added cost, which necessitates increased use of these economic resources.The quantities of productive resources required to achieve the optimal production size per dunam were (6.176, 85.105, 3.308, 2.118, 12.84) for resources (x6, x5, x4, x3, x2) respectively, which exceed the actual quantities used. The study recommended supporting farmers to achieve optimal production utilization through the optimal use of productive resources in the production of yellow corn in the studied farms.